Análisis de las tecnologías utilizadas por Ecuador y Perú durante el conflicto del Cenepa - Flores Morales, Wendy Pamela (2024)
Throughout the years, Ecuador and Peru maintained numerous conflicts because of the colonial legacy. To avoid them, different treaties were signed, which turned out to be ambiguous due to non-compliance and situational changes in them. Thus, the last confrontation between both nations took place between 1994-1995 due to the invasion of both countries to the undemarcated area of the Cenepa river basin, which caused a confrontation at all strategic levels and the signing of peace. This research determines the weapons and communication technologies used by the armies of Ecuador and Peru as part of their military strategies during the Cenepa conflict, which took place between 1994 and 1995. The study employs a qualitative methodology with a documentary modality at the descriptive and explanatory levels. This work exposes the military background of Ecuador and Peru, the Cenepa conflict, planning at all levels (strategic, operational and tactical), budget, weapons implemented in combat, comparison of weaponry, military communication, news generated and the impact of the confrontation and the media on the civilian population. All the information gathered will serve for the development of future research and the modification of the perception of the conflict.